Coal mining environment causes adverse effects on workers - Chen, Huihui; Ding, Xinping; Zhang, Wenzhong; Dong, Xichen (Frontiers in Public Health, 2024)
Background: To study the adverse effects of coal mining environment on workers, to discover early effective biomarkers.The molecular epidemiological study was conducted with 502 in-service workers, who were divided into miner and auxiliary. We measured the individual levels of dust exposure for participants. Clinical examinations were conducted by qualified doctors. Peripheral blood was collected to measure biochemistry, hemogram and karyocyte apoptosis.Results: All workers were healthy who have not found any diseases that can be diagnosed medically in the physical examination and showed no difference in dust exposure level, age, height, weight and body mass index between groups. The working years of miners were lower than that of auxiliaries (P < 0.001). Compared with auxiliaries, the concentration and percentage of lymphocytes(P = 0.040，P = 0.012), basophils(P = 0.027，P = 0.034), red blood cells(P < 0.001) and the concentration of hemoglobin of miners were lower (P < 0.001). The percentage of neutrophils (P = 0.003), the concentration of mean corpuscular hemoglobin concentration (P = 0.002) and the proportion of karyocyte apoptosis in miners were higher (P < 0.001). Miners presented higher blood urea nitrogen (P < 0.001), ratio of blood urea nitrogen to creatinine (P < 0.001) and the high density lipoprotein cholesterol (P < 0.001), lower creatinine (P < 0.05) and cholesterol (P < 0.001).The coal mining environment impacted mining workers' immune function, renal function and the hemopoietic system -including BUN/CRE, HGB, RBC and LYMPH, which could be used as early biomarkers to screen the health of coal miners.